STRATEGI DISPERINDAGKOP UKM DI PEMERINTAH KABUPATEN/KOTA DALAM PENGEMBANGAN HOME INDUSTRY DI INDONESIA - Nanik Pujiastuti Dan Frendly Albertus (Prodi Ilmu Administrasi Negara, 2017)
The purpose of the Indonesian state is as stated in the Preamble of the 1945 Constitution of the fourth paragraph: